Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1002/hpm.2848
|View full text |Cite
|
Sign up to set email alerts
|

The impact of out‐of‐pocket health expenditure on household impoverishment: Evidence from Morocco

Abstract: Summary Health financing in Morocco relies mainly on out‐of‐pocket (OoP) payments. World Health Organization (WHO) has shown that these payments can expose households to catastrophic health expenditure (hereinafter CHE) and impoverish them. The study examines the financial burden of OoP health payments on Moroccan households. Two approaches—that developed by Wagstaff and Doeslear and the one advocated by WHO—are adopted to estimate the extent of CHE. These show that 1.77% of households incurred CHE at the 40% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 16 publications
2
16
1
Order By: Relevance
“…Our finding that hospitalizations increased the incidence of catastrophic health expenditures is consistent with findings from other studies [5,20,21,41,42]. Households with hospitalized members may sell assets, use savings and hire external labor as coping mechanisms.…”
Section: Discussionsupporting
confidence: 92%
“…Our finding that hospitalizations increased the incidence of catastrophic health expenditures is consistent with findings from other studies [5,20,21,41,42]. Households with hospitalized members may sell assets, use savings and hire external labor as coping mechanisms.…”
Section: Discussionsupporting
confidence: 92%
“…This nancial catastrophe is not without social and economic consequences because those who can pay spend their savings or reduce their basic needs. However, for households that cannot pay, the mothers and babies are held at the point of care, sometimes without treatment, since they cannot afford care.This study aligns with several other studies within the DRC [6,8,9] and elsewhere [32,[45][46][47] revealing that even the lowest healthcare costs are out of reach for many people. As a result, several social and economic consequences arise at the household level: exclusion from health care, indebtedness and high use of the informal sector [15,39,48].It is true that the presence of quali ed personnel during all deliveries is considered to be one of the most important interventions for safer births because it reduces maternal deaths and increases successful delivery of infants [41,[49][50][51].…”
Section: Discussionsupporting
confidence: 92%
“…The Kenyan health insurance programme also promotes access to maternal healthcare in private hospitals90 and reduces out-of-pocket health expenditures 91. In Morocco, the only impact study we included in this review found a significant impact of insurance on catastrophic health expenditure 92. In Nigeria, the public health insurance scheme is also reported to have an impact on access to care and financial protection for beneficiaries,93 except for the poor 93.…”
Section: Resultsmentioning
confidence: 95%
“…91 In Morocco, the only impact study we included in this review found a significant impact of insurance on catastrophic health expenditure. 92 In Nigeria, the public health insurance scheme is also reported to have an impact on access to care and financial protection for beneficiaries, 93 except for the poor. 93 Such a lack of equity was also observed in Rwanda, where policyholders in the poorest quintiles used less care than other policyholders and were more exposed than the latter to catastrophic health expenditure.…”
Section: Resultsmentioning
confidence: 99%